Algebraic Properties of Semi-Direct Sums of Rings - Nowakowska Marta (Annales Mathematicae Silesianae)
Let R be an associative ring not necessarily with unity. We say that R is a semi-direct sum of rings S and I, if R = S + I, where S is a subring of a ring R, I is an ideal of R and S ∩ I = {0}.